82 INHIBITION OF THE HERG CHANNEL BY ASPIRIN: PH OR DIRECT EFFECT?. (1st March 2007) - Lin, C.; Ke, X.; Ranade, V.; Molnar, J.; Somberg, J. C.
Abstract : Aspirin (ASA) has been widely used for many years for relieving pain and fever and in preventing heart attack and stroke. ASA overdose can result in an anion gap, metabolic acidosis, tinnitus, and, in severe cases, encephalopathy and cardiovascular collapse. There are studies showing the inhibitory effect of ASA on heat-evoked currents in rat dorsal root ganglion neurons and the augmented effect of ASA on the NMDA type of glutamate responses in spiral ganglion neurons. The effect of ASA on cardiac ion channels has not been studied. We evaluated the effect of ASA on cardiac IKr channel using HERG expressed on Xenopus oocytes. A two-microelectrode voltage clamp technique was used for recording, and the recording solution contained 96 mM NaCl, 5.0 mM KCl, 2.0 mM CaCl2, 1.0 mM MgCl2, and 5 mM HEPES, and the pH of the solution was adjusted with NaOH to 7.4. ASA was dissolved in the recording solution. At a concentration less than 1 mM, ASA has little effect on HERG current. ASA 1 mM and 2 mM inhibited current by 12 ± 2 and 22 ± 4%, respectively. ASA 3 mM inhibited current by 80 ± 6%. Considering the acidifying influence of ASA, the pH values of 1, 2, and 3 mM ASA solutions were determined as 7.1, 6.5, and 4.9. The pH of the recording solutions was adjusted to the corresponding pH, and the results showed that pH 7.1, 6.5, and 4.9 reduced HERG current by 6 ± 2, 10 ± 2, and 49 ± 5%. ASA 1, 2, and 3 mM caused greater inhibition of current than the recording solutions with the corresponding pH adjustment. There were significant differences in current inhibition between 2 mM ASA and the pH 6.5 recording solution ( p < .05) and between 3 mM ASA and pH 4.9 recording solution ( p < .01). ASA inhibits HERG current not only through acidification but also by a direct effect. The potent inhibition at 3 mM (54 mg/dL) further suggests that ASA at therapeutic doses and at doses seen with acute and chronic salicylism (40-120 mg/dL) may be arrhythmogenic owing to potent inhibition of the cardiac IKr channel.